A Quantitative Microfounded Model for the Integrated Policy Framework - Adrian, Tobias (IMF Working Papers; Working Paper ;, 2021)
We develop a microfounded New Keynesian model to analyze monetary policy and financial stability issues in open economies with financial fragilities and weakly anchored inflation expectations. We show that foreign exchange intervention (FXI) and capital flow management tools (CFMs) can improve monetary policy tradeoffs under some conditions, including by reducing the need for procyclical tightening in response to capital outflow pressures. Moreover, they can be used in a preemptive way to reduce the risk of a 'sudden stop' through curbing a buildup in leverage. While these tools can materially improve welfare, mainly by dampening inefficient fluctuations in risk premia, our analysis also highlights potential limitations, including the possibility that their deployment may forestall needed adjustment in the external balance. Finally, our results also emphasize the power of FXIs to provide domestic stimulus in a liquidity trap.